Kinerja Louvre Kayu Jati untuk Ventilasi Alami dan Pengendalian Kebisingan melalui Simulasi - Faradifa Meitadevi; Nurhamdoko Bonifacius; Dina Poerwoningsih (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2026)
Performance of Teak Wood Louvre for Natural Ventilation andNoise Control trough SimulationLouvres, as facade elements, have dual potential in supporting natural ventilation performance and reducing noise. However, their performance strongly depends on blade geometric configuration. A quantitative study is required to evaluate Louvre blade configuration in terms of ventilation and acoustic performance, as well as their effectiveness when using teak wood material. The methods include Computational Fluid Dynamics (CFD) simulation to obtain Air Changes per Hour (ACH) value and acoustic simulations to determine Transmission Loss (TL). The result shows that blade spacing is the dominant factor. A configuration with 2.5mm spacing and a 3/5 inclination provides the most balanced performance, although it does not yet meet the standard. The use of teak wood is proven to improve both natural ventilation and acoustic performance compared to aluminium.